A qualitative study of paramedics' attitudes to providing prehospital thrombolysis. Issue 10 (27th September 2005) - Price, L; Keeling, P; Brown, G; Hughes, D; Barton, A
Abstract : Objectives: To explore paramedics' attitudes to administering prehospital thrombolysis (PHT). Method: In-depth interviews with 20 paramedics were recorded and transcribed and analysed for emergent themes using the constant comparative method. Results: Although there was a will to provide PHT because of its benefits to patients, its associated risks, aspects of pay and working conditions, and certain organisational factors undermined the willingness of some paramedics to administer thrombolysis. The eight minute response time standard is a competing imperative which can delay thrombolysis. Conclusions: A minority of paramedics are likely to be unwilling to deliver PHT unless countervailing imperatives are addressed.